Genetic and Biochemical Analysis of the Azotobacter vinelandii Molybdenum Storage Protein - Navarro-Rodríguez, Mónica; Buesa, José María; Rubio, Luis M. (Frontiers in Microbiology, 2019)
The N2 fixing bacterium Azotobacter vinelandii carries a molybdenum storage protein, referred to as MoSto, able to bind 25-fold more Mo than needed for maximum activity of its Mo nitrogenase. Here we have investigated a plausible role of MoSto as obligate intermediate in the pathway that provides Mo for the biosynthesis of nitrogenase iron–molybdenum cofactor (FeMo-co). The in vitro FeMo-co synthesis and insertion assay demonstrated that purified MoSto functions as Mo donor and that direct interaction with FeMo-co biosynthetic proteins stimulated Mo donation. The phenotype of an A. vinelandii strain lacking the MoSto subunit genes (ΔmosAB) was analyzed. Consistent with its role as storage protein, the ΔmosAB strain showed severe impairment to accumulate intracellular Mo and lower resilience than wild type to Mo starvation as demonstrated by decreased in vivo nitrogenase activity and competitive growth index. In addition, it was more sensitive than the wild type to diazotrophic growth inhibition by W. The ΔmosAB strain was found to readily derepress vnfDGK upon Mo step down, in contrast to the wild type that derepressed Vnf proteins only after prolonged Mo starvation. The ΔmosAB mutation was then introduced in a strain lacking V and Fe-only nitrogenase structural genes (Δvnf Δanf) to investigate possible compensations from these alternative systems. When grown in Mo-depleted medium, the ΔmosAB and mosAB+ strains showed low but similar nitrogenase activities regardless of the presence of Vnf proteins. This study highlights the selective advantage that MoSto confers to A. vinelandii in situations of metal limitation as those found in many soil ecosystems. Such a favorable trait should be included in the gene complement of future nitrogen fixing plants.